Teacher guide: implementing the CEFR-aligned curriculum: planning and managing learning - Abdul Latif @ Bapoo, Lilisuriani (Kementerian Pendidikan Malaysia, 2019)
The Guide is designed to help teachers develop their own lesson plans and activities using the CEFR-aligned curriculum framework, syllabus and scheme of work as references. The content is drawn from the resource materials provided by Cambridge English (CE) at the CEFR Familiarisation, Learning Materials Adaptation (LMA), Curriculum Induction (Cl) and Formative Assessment (FA) training sessions that teachers went through.